Pengaruh Literasi Digital Terhadap Tingkat KemandirianBelajar Mahasiswa Dengan Kecerdasan Emosional Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa) - Maria Elisabeth Marliana; Wihelmina Mitan; Emilianus Eo K. Goo (Ikatan Da'i Indonesia, 2025)
The research aimed to analyze the effect of digital literacy on the level of students’ learning independence with emotonal inttellegence as an intervening variable. This research used a quantitative method. The population consisted of 133 accounting students from Nusa Nipa University, with a sample of only 57 respondents. The type of data in this research was primary data, which was collected from quationnaires. Data were analyzed using statistical analysis model test, hypothesis test (T-test), and Sobel test with the assistance of SPSS. The result of the research indicated that (1) digital liteacy had a significant effect on the level of students’ learning independence, (2) digital literacy had a significant effect on the level of emotional intelligence, (3) level of emotional intelligence had a significant effect on the level of students’ learning independence, (4) emotional intelligence mediated the effect of digital literacy toward level of students’ learning independence.